Recent advances in oxidative radical difunctionalization of N-arylacrylamides enabled by carbon radical reagents - Jiangfei Chen; Yi-Lin Qu; Ming Yuan; Xiang-Mei Wu; Heng-Pei Jiang; Ying Fu; Shengrong Guo (Beilstein Journal of Organic Chemistry)
The field of radical-mediated functionalization of N-arylacrylamides has experienced considerable advancements in recent years, particularly in the domain of oxidative radical difunctionalization reactions employing carbon radical reagents. This approach provides a powerful and versatile strategy for the concurrent introduction of two distinct functional groups across the double bond of N-arylacrylamides, facilitating the rapid construction of complex molecular architectures. This review aims to summarize the diverse strategies for inducing intramolecular transformations of N-arylacrylamides using various carbon radical reagents, including methods initiated by photonic, thermal, or electrochemical processes, which have been extensively investigated by researchers.